2022
DOI: 10.3389/fmed.2021.806616
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of the Prevalence and Pattern of Multimorbidity in Older Chinese Adults

Abstract: BackgroundMultimorbidity presents an enormous problem to societal and healthcare utilization under the context of aging population in low- and middle-income countries (LMICs). Currently, systematic studies on the profile of multimorbidity and its characteristics among Chinese elderly are lacking. We described the temporal and spatial trends in the prevalence of multimorbidity and explored chronological changes of comorbidity patterns in a large elderly population survey.MethodsData were extracted from the Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…The current study confirmed that a high WCR is significantly associated with reduced cognitive function among elderly individuals, which is consistent with previous studies showing that SO or a higher adiposity-to-muscle ratio negatively impacts cognitive function in older adults (Gao et al, 2015(Gao et al, , 2020Ribeiro Santos et al, 2020;Brewster et al, 2021;Chen et al, 2021). This finding suggested that the combination of sarcopenia and obesity could generate a synergetic effect on cognitive impairment rather than a simple superposition, but the mechanism underlying this effect is unclear (Gao et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study confirmed that a high WCR is significantly associated with reduced cognitive function among elderly individuals, which is consistent with previous studies showing that SO or a higher adiposity-to-muscle ratio negatively impacts cognitive function in older adults (Gao et al, 2015(Gao et al, , 2020Ribeiro Santos et al, 2020;Brewster et al, 2021;Chen et al, 2021). This finding suggested that the combination of sarcopenia and obesity could generate a synergetic effect on cognitive impairment rather than a simple superposition, but the mechanism underlying this effect is unclear (Gao et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Due to the lack of a uniform definition for SO and different study populations, its reported prevalence estimates range from 2.75% to 20% or more (Chang et al, 2015). According to some previous reports, the prevalence of SO in Chinese community-dwelling older adults was estimated at 6.0-25.0% (Chang et al, 2016;Chen et al, 2021;Cheng et al, 2022). SO is associated with poor health outcomes including frailty, disability (Choe et al, 2018), fractures, falls (Chou et al, 2022), cancer (Daviglus et al, 2010), cardiometabolic diseases (Donini et al, 2020), chronic kidney disease (Dye et al, 2017), and increased mortality (Espeland et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed variable codes are presented in Supplementary Table S5 . For the health status, the CLHLS adopted a list of 13 chronic diseases or conditions (e.g., hypertension, diabetes, heart diseases, stroke, cancers, Parkinson’s disease) to measure comorbidity; an individual was considered to have physical comorbidities (yes or no) if he or she self-reported more than two of these thirteen diseases or conditions at the time of the surveys ( 35 , 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…LOS was classified into three groups: less than 15 days, 15–30 days and 30 days and longer. Presence of comorbidities was measured by binary variables indicating whether individuals had the following doctor-diagnosed major chronic diseases: hypertension [ 50 , 51 , 52 ], diabetes [ 50 , 52 ], coronary heart disease [ 50 ], Alzheimer’s disease, schizophrenia [ 53 , 54 ] and mood disorders [ 52 , 55 ]. The detailed measures of variables are shown in Table 3 .…”
Section: Methodsmentioning
confidence: 99%